(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2024)
This article analyzes the capabilities of YOLO (You Only Look Once) models in the field of image recognition and the achievements made with them. The YOLO algorithm stands out among object recognition technologies for its speed and accuracy. Each version of the YOLO models includes its own technological innovations, and each has increased accuracy and efficiency. This article highlights the changes in each version of the YOLO models and their technical capabilities.